1983
DOI: 10.1111/j.1476-5381.1983.tb10024.x
|View full text |Cite
|
Sign up to set email alerts
|

Thyrotropin releasing hormone‐induced hyperthermia in mice: possible involvement of adrenal and pituitary glands

Abstract: 1To investigate the hyperthermic effect of thyrotropin releasing hormone (TRH) and its potentiation by exogenous catecholamines (CA), the role of the adrenal medulla and of the pituitary gland was studied in unoperated, adrenal-demedullated or hypophysectomized mice. 2 In unoperated mice, TRH 40 mg kg-l i.p. produced a hyperthermia which was accompanied by an increase in plasma noradrenaline (NA) and adrenaline (Ad). NA or Ad, both at a dose of 1 mg kg-I i.p., enhanced the TRH-induced hyperthermia.3 Adrenal de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In the hypothalamus-pituitarythyroid axis, the cold-induced increase in TRH stimulates TSH secretion by the pituitary, which in turn stimulates thyroid hormone release from the thyroid (11). Research in various species showed that both core body temperature (32,33) and BAT-specific temperature (13) are increased by central or peripheral administration of TRH. Intracerebroventricular infusion of TRH in rodents was found to activate BAT via sympathetic neurons, an effect that could be blocked by pre-treatment with TRHreceptor type 1 antibodies and attenuated by sympathetic denervation of BAT depots (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…In the hypothalamus-pituitarythyroid axis, the cold-induced increase in TRH stimulates TSH secretion by the pituitary, which in turn stimulates thyroid hormone release from the thyroid (11). Research in various species showed that both core body temperature (32,33) and BAT-specific temperature (13) are increased by central or peripheral administration of TRH. Intracerebroventricular infusion of TRH in rodents was found to activate BAT via sympathetic neurons, an effect that could be blocked by pre-treatment with TRHreceptor type 1 antibodies and attenuated by sympathetic denervation of BAT depots (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…However, the observation that the lower dose of TRH (5 mg/kg) increased locomotor activity but had no significant effect on body temperature suggests that the mechanism involved in TRH‐induced thermogenesis is not simply via the induction of locomotor activity. In mice, it has been shown that peripheral injections of TRH at a dose of 40 mg/kg also induced a rapid and short‐lasting hyperthermia (47). In rats, central administration of TRH induces hyperthermia (22), and antagonises drug‐induced hypothermic effects (48).…”
Section: Discussionmentioning
confidence: 99%